2007
DOI: 10.1186/1749-799x-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Microdecompression for lumbar synovial cysts: an independent assessment of long term outcomes

Abstract: Background: Outcomes of surgical intervention for lumbar synovial cysts have been evaluated in the short and intermediate term. Concerns regarding cyst recurrence, the development of late instability at the involved level, and instability/stenosis at adjacent levels (when concomitant) fusion is performed suggest that long term follow-up is needed. This study aims to fill that void.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
(16 reference statements)
3
11
0
Order By: Relevance
“…19) Many reports have confirmed that gross total resection, usually without the need for extensive facetectomy or spinal fusion, provides satisfactory results in 80-90% of patients with excellent to good outcomes. 7,28,39) The significant reduction of VAS score at discharge (p º 0.05) and the remarkable MacNab score at follow up in the present study further confirm the effectiveness of this technique. Gross total resection is also particularly safe because the rate of perioperative complications is low at 3%, 26) including CSF fistula, epidural hematoma, seroma, discitis, and phlebitis, compared to instrumented procedures.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…19) Many reports have confirmed that gross total resection, usually without the need for extensive facetectomy or spinal fusion, provides satisfactory results in 80-90% of patients with excellent to good outcomes. 7,28,39) The significant reduction of VAS score at discharge (p º 0.05) and the remarkable MacNab score at follow up in the present study further confirm the effectiveness of this technique. Gross total resection is also particularly safe because the rate of perioperative complications is low at 3%, 26) including CSF fistula, epidural hematoma, seroma, discitis, and phlebitis, compared to instrumented procedures.…”
Section: Discussionsupporting
confidence: 73%
“…Outcome data at an average of 10 years follow up after surgical excision of 46 LSCs, with arthrodesis always performed in the presence of degenerative spondylolisthesis, found that subsequent additional surgery was necessary in 15%, with no statistical differences for any outcome measure between patients undergoing concomitant fusion and those undergoing only decompression. 39) In this aspect, minimally invasive techniques might be particularly useful, as the use of tubular retractors may minimize the risk of spinal instability even in a case of spondylolisthesis. 34) The review of the literature on this subject did not yield new satisfactory insights: in fact, no significant difference in clinical outcomes between endoscopic versus open surgery, except for the lower blood loss and soft tissue trauma of the minimally invasive techniques, has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These patients required more invasive removal of the facet joint and accurate neural dissection. Weiner declares that adherence to the dura is a common finding and that it has to be "carefully teased free so that no cyst pseudocapsule" remains [12]. Epstein emphasizes that "utilizing the operating microscope is extremely helpful in avoiding CSF fistulas during decompression and removal of synovial cysts, as these fistulas are more likely to arise secondary to dense adhesions between the cyst capsule and underlying dura/nerve roots" [13].…”
Section: Discussionmentioning
confidence: 98%
“…Although all of the cysts in their series were actually true synovial cysts that were treated with hemilaminectomy/ laminectomy with facet sparing, none of these patients, even those with preoperatively fixed spondylolisthesis, presented with instability at a median follow-up of 28 months. Forty-six patients with a LISC treated with microscopic decompression were followed up for nearly 10 years by Weiner et al 49 The only indication for concomitant fusion (noninstrumented) in this series was the presence of spondylolisthesis, which was involved in 50% of their patient population. Even though the authors did not differentiate static from dynamic spondylolisthesis, 89% of the patients reported satisfaction with the surgery 10 years later, with no statistical differences for any outcome measure between patients who underwent fusion and those who did not.…”
Section: Discussionmentioning
confidence: 98%